2010
DOI: 10.1017/s0025315409991639
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of delphinids (Mammalia: Cetacea) from Rio de Janeiro State, Brazil

Abstract: Stomach content analyses were performed in 28 dolphins stranded between 1994 and 2007 on the beaches of Rio de Janeiro State (23°06′S 44°18′W/22°14′S 41°54′W), Brazil, comprising six delphinid species: Stenella frontalis (N = 10), Steno bredanensis (N = 7), Tursiops truncatus (N = 4), Delphinus delphis (N = 5), Lagenodelphis hosei (N = 1) and Stenella coeruleoalba (N = 1). Fish otoliths and cephalopod beaks were used to identify the prey species and to estimate the original length and weight. Seven different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
3
36
0
5
Order By: Relevance
“…Finding high concentrations of persistent accumulative toxicants in this dolphin population is not surprising. Rough-toothed dolphins from RJ feed on top-predator fish (Bisi et al, 2012;Melo et al, 2010), thus they are more likely to take in high amounts of contaminants that have accumulated in the bodies of the prey.…”
Section: Rough-toothed Dolphinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding high concentrations of persistent accumulative toxicants in this dolphin population is not surprising. Rough-toothed dolphins from RJ feed on top-predator fish (Bisi et al, 2012;Melo et al, 2010), thus they are more likely to take in high amounts of contaminants that have accumulated in the bodies of the prey.…”
Section: Rough-toothed Dolphinsmentioning
confidence: 99%
“…Rough-toothed dolphins can occasionally reach more than 2.8 m of total length (Jefferson, 2009). Taking into consideration that this continental shelf (CS) delphinid has many prey species in common with estuarine dolphin species, such as the Guiana dolphin (Melo et al, 2010, submitted for publication), the greater size of rough-toothed dolphins means that these CS delphinids have anatomical characteristics that enable them to feed on larger fish, and hence, on prey specimens that had a longer exposure time to pollutants than those consumed by Guiana dolphins. Although it is still controversial whether or not false killer whales feed on other cetacean species, they are known to prey on large and long-lived fish such as tunas and swordfish (Baird et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies carried out in the Gulf of Mexico have demonstrated that cephalopods are also important part of the diet for this species, though principally for offshore populations (Barros and Odell, 1990). Table 2 shows the prey species detected in stomach contents of bottlenose dolphins in the study area from previous works (Di Beneditto et al, 2001;Melo et al, 2010). In general, cutlass fish followed by midshipman fish and Atlantic spade fish seem to represent significant prey species.…”
Section: Resultsmentioning
confidence: 87%
“…and life stage. Previous studies conducted in RJ indicate that the bottlenose dolphin feeds preferentially on coastal fish (Di Beneditto et al, 2001;Melo et al, 2010).…”
mentioning
confidence: 95%